Judy Moody & Stink : The Big Bad Blackout - McDonald, Megan; Reynolds, Peter 1961- (Somerville, Mass. : Candlewick Press, 2014)
As Hurrican Elmer hits, Judy, Stink, and the entire Moody clan hunker down and ride out the storm, but when the power goes out, Grandma Lou proposes some activities to pass the time in the dark.
Keywords: Moody, Judy (Fictitious character) -- Juvenile fiction; Electric power failures -- Juvenile fiction; Hurricanes -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Moody, Judy (Fictitious character) -- Fiction; Electric power failures -- Fiction; Hurricanes -- Fiction; Brothers and sisters -- Fiction